Lemierre syndrome: Current evidence and rationale of the Bacteria-Associated Thrombosis, Thrombophlebitis and LEmierre syndrome (BATTLE) registry. Issue 196 (December 2020) - Valerio, Luca; Corsi, Gabriele; Sebastian, Tim; Barco, Stefano
Abstract: Lemierre syndrome is a rare but potentially fatal condition characterized by septic thrombophlebitis of the head and neck district, preferentially affecting adolescents and young adults and manifesting as a complication of a local bacterial infection – typically, a pharyngotonsillitis or an abscess. It is historically associated with the Gram-negative anaerobic rod Fusobacterium necrophorum and with thrombophlebitis of the internal jugular vein. However, its definition has never been firmly established, and its spectrum within the continuum of bacteria-associated thrombophlebitis may be larger than what presumed so far. Recent evidence suggests that its prognosis remains serious even one hundred years after its first description, with considerable rates of in-hospital complications, death, and long-term sequelae. There are no specific guidelines on its management other than usual antibiotic stewardship, with ongoing debate on the potential role of therapeutic-dose anticoagulation. We provide an overview of current evidence on the definition, epidemiology, clinical presentation, prognosis and management of this condition and present the background and rationale of the Bacteria-Associated Thrombosis/Thrombophlebitis and LEmierre syndrome (BATTLE) registry: an ambispective, disease-specific, non-population based, multicentre clinical registry of global reach and multidisciplinary scope, specifically designed to address the limitations of current evidence and to provide patients and physicians with clinically viable information to guide management and improve the outcomes of those affected by these conditions. Highlights: Lemierre syndrome is a rare but potentially fatal acute thromboembolic disease. Lemierre syndrome belongs to the continuum of bacteria-associated thrombophlebitis. All available evidence on Lemierre syndrome stems from case reports and series. No consensus exists on how to diagnose, prevent and manage Lemierre syndrome. The BATTLE registry is designed to ultimately support development of guidelines.